Poly[piperazinediium [[aquabismuthate(III)]-di-μ-pyridine-2,6-dicarboxylato-bismuthate(III)-di-μ-pyridine-2,6-dicarboxylato] monohydrate] - Aghabozorg, Hossein (International Union of Crystallography, 2008)
The title compound, {(C(4)H(12)N(2))[Bi(2)(C(7)H(3)NO(4))(4)(H(2)O)]·H(2)O}(n) or {(pipzH(2))[Bi(2)(pydc)(4)(H(2)O)]·H(2)O}(n), where pydcH(2) is pyridine-2,6-dicarboxylic acid and pipz is piperazine, was obtained by reaction of Bi(NO(3))(3)·5H(2)O with (pipzH(2))(pydcH)(2)·3H(2)O in a 1:2 molar ratio in aqueous solution. There are two independent Bi(III) atoms in the structure, one of which is eight-coordinate with a distorted bicapped trigonal-prismatic geometry, and another which is nine-coordinate with a distorted tricapped trigonal-prismatic geometry. The carboxylate groups of the (pydc)(2−) ligands link dinuclear [Bi(2)(C(7)H(3)NO(4))(4)(H(2)O)](2−) units into one-dimensional coordination polymers. The pipzH(2) (2+) cations (site symmetry [Image: see text]) and non-coordinated water molecules lie between these polymers, forming N—H⋯O and O—H⋯O hydrogen bonds to the O atoms of the carboxylate groups.